1985
DOI: 10.1007/bf00225417
|View full text |Cite
|
Sign up to set email alerts
|

Stereologic and fine-structural studies of prostatic acinar basal cells in the dog

Abstract: There are two distinct types of epithelial cells in the lining of the glandular acini of the prostate in adult male Beagle dogs, i.e., the columnar secretory epithelial cells and the basal cells. In contrast to the secretory epithelial cells, basal cells exhibit an abundance of micropinocytotic vesicles on their basal surface. Blood capillaries are often found in the stromal tissue in close proximity to these cells and their walls frequently display chains of fenestrations bridged by diaphragms. Stereological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In addition, complex plasma membrane infoldings and interdigitations between basal and secretory cells have been found (Mao and Angrist, 1966). These ultrastructural features and the frequent close proximity of blood capillaries in the stroma to basal cells (Timms et al, 1976;Ichihara et al, 1985) support the concept of their transport role.…”
Section: The Effect Of Actinomycin D and Hydrocortisone Treatmentssupporting
confidence: 64%
See 1 more Smart Citation
“…In addition, complex plasma membrane infoldings and interdigitations between basal and secretory cells have been found (Mao and Angrist, 1966). These ultrastructural features and the frequent close proximity of blood capillaries in the stroma to basal cells (Timms et al, 1976;Ichihara et al, 1985) support the concept of their transport role.…”
Section: The Effect Of Actinomycin D and Hydrocortisone Treatmentssupporting
confidence: 64%
“…Basal cells have also been proposed to have a role in transportation of material between secretory cells in the acinus and the extra-acinar space. Adenosine triphosphatase activity has been described on the basal cell plasma membrane (Mao and Angrist, 1966) and micropinocytotic vesicles are found on their basal surfaces (Timms et al, 1976;Ichihara et al, 1985). The pinocytotic vesicles in the rat show strong alkaline phosphatase activity (Kimura and Ichihara, 1980).…”
Section: The Effect Of Actinomycin D and Hydrocortisone Treatmentsmentioning
confidence: 99%
“…The functional role of these cells is unknown, but interestingly they do not express androgen receptors and express different high molecular weight cytokeratins than the columnar cells [31,32]. They may serve as stem cells for the columnar cells, but they probably also secrete local regulatory substances [33]. It is generally assumed that prostatic cancers arise from the columnar epithelial cells and that the basal epithelial cells disappear during malignant transformation [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the embryonic mesenchyme in most tissues, including the prostate [12], has an informational role for the development of the epithelium it supports [ 131. Basement membranes may also have an informational role [ 141, and, in the prostate, they are in close association with basal reserve cells [15,16]. In addition, extracellular matrices (ECM), as well as some of their components, such as collagens, fibronectin, laminin, and proteoglycans, influence not only plating efficiency and cell spreading but also cell morphology, proliferation, and differentiation [17][18][19].…”
Section: Introductionmentioning
confidence: 99%